INVESTIGATING SCHOOL TEACHERS’ PERCEPTIONS OF CONSTRUCTIVIST THEORY: A MULTIPLE CASE STUDY IN LEBANON - Hajal, Pascale (PEOPLE: International Journal of Social Sciences, 2019)
The purpose of this study is to investigate teachers’ perception and application of constructivist theory in schools. This study followed a qualitative approach. Teaching strategies used in class were observed, and schoolteachers and coordinators after each class observation were interviewed. Main findings indicate that the schoolteachers lacked comprehensible perception of the real application and meaning of constructivist theory. These results indicate a negative perception of constructivist theory. Four main limitations have influenced the efficacy of this study. Schools’ pedagogy should be enhanced, and in order to overcome the gap found by this study and enhance schoolteachers’ perception of several teaching methodologies, which will help them shift to student-centeredness, a concerted effort and coordination between the Ministry of Education and Center of Education and Research Development, education makers in the education field, school administrators and schoolteachers, and students and their parents would be highly beneficial and important. A new culture is suggested to be built where capacity building programs should be introduced to educational sectors in Lebanon. This study encourages schoolteachers to enhance their knowledge on constructivist theory in order to engage, motivate and improve the quality of education.